2017
DOI: 10.21521/mw.5708
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oral administration of HMB to pregnant dams on calbindin expression in the dentate gyrus of the hippocampus during postnatal development in spiny mice offspring

Abstract: Influence of oral administration of HMB to pregnant dams on calbindin expression in the dentate gyrus of the hippocampus during postnatal development in spiny mice offspring Summary The aim of the study was to investigate the morphology, density and immunostaining intensity of calbindin (CB)-positive neurons of dentate gyrus (DG) in new-born (P0) and 21-day-old (P21) male Acomys cahirinus mice from dams receiving β-hydroxy-β-methylbutyrate (HMB) during pregnancy. Different substances administrated to pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…These previous results suggest that prenatal exposure to HMB disturbs hormonal homeostasis, which impairs early folliculogenesis in piglets [ 69 ]. Other studies have shown a negative effect of HMB on hippocampal function in male offspring [ 14 ]. Whether the adverse effects of HMB supplementation during pregnancy are due to the dose of HMB administered or are a result of the stage of pregnancy during which supplementation occurs still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These previous results suggest that prenatal exposure to HMB disturbs hormonal homeostasis, which impairs early folliculogenesis in piglets [ 69 ]. Other studies have shown a negative effect of HMB on hippocampal function in male offspring [ 14 ]. Whether the adverse effects of HMB supplementation during pregnancy are due to the dose of HMB administered or are a result of the stage of pregnancy during which supplementation occurs still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Females from all experimental groups, as well as the newborn pups from females in groups PregCont and PregHMB were euthanized by CO 2 inhalation. To accomplish the 3R’s rule, tissue samples received from pups were used in another study [ 14 ]. Immediately after euthanasia, femora were carefully dissected out of the mice, cleaned of adhering tissues, individually packed, and stored frozen at −20 °C until they were examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few experimental studies using animal models explaining the effect of the HMB supplementation in the prenatal period. However, in the last few years some have been related to the influence of this supplement on the skeletal system [ 14 20 ]. In the literature the information on the impact of this supplement on the femoral bone of newborn organisms whose mothers had the HMB supplementation during pregnancy [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last few years some have been related to the influence of this supplement on the skeletal system. [14][15][16][17][18][19][20]. In the literature the information on the impact of this supplement on the femoral bone of newborn organisms whose mothers had the HMB supplementation during pregnancy [16,17].…”
Section: Introductionmentioning
confidence: 99%